THE COMMITMENT OF THE TUBAN REGENCY GOVERNMENT IN SUPPORTING SUSTAINABLE DEVELOPMENT GOALS 12 THROUGH ZERO WASTE ZERO EMISSION IN 2025 - Abdul Khakim Mahfud Zubaidi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study Describes about the commitment of the Tuban Regency Government in supporting Sustainable Development Goals (SDGs) 12 through the Zero Waste Emission program in 2025. The research employs a qualitative descriptive approach to provide a comprehensive overview of policy and program strategies aimed at minimizing waste generation and promoting sustainable consumption and production. Findings indicate that the Tuban Regency Government has demonstrated ecological responsibility through strategic planning, community engagement, and infrastructural support, such as the development of Refuse-Derived Fuel (RDF) facilities and the expansion of community-based waste banks. However, challenges persist in achieving full participation from the community and aligning local practices with broader SDG 12 targets. The study contributes to understanding how local governments operationalize sustainability principles and highlights the need for integrated efforts between government, community, and industry to ensure long-term environmental stewardship.